Is there a Racial Gap in Market Facilitation Program Payments and Total Government Payments? - Murphy, Ashling (Kansas State University, 2023)
In 2017, there was 32,910 Black or African American farms that were primarily located in the southeast and mid-Atlantic and had an average farm size of 125 acres. In comparison, 1,963,286 farms were White and had an average farm size of 431 acres (USDA NASS, 2017). In 2017, Black producers received $59 million (0.7%) and White producers received $8.9 billion (99%) of total government payments (USDA NASS, 2019). Black farms received 0.17 percent of the total share of Market Facilitation Program payments compared to White farms who received 99.18 percent of payments (Giri et al., 2022). Some policymakers have raised concerns about this apparent disparity in government payments between Black and White farms. However, no existing analysis explains the source of the racial gap. In this thesis, I conducted two sets of analysis using the micro-level Census of Agriculture data from 2017 to provide new insights on the racial gap. The first analysis examined the amount of payment from the 2018 Market Facilitation Program (MFP) that farms were eligible to receive and provided a decomposition to measure how much of the difference in eligible payments was due to differences in yield, acreage, and the share of crops produced. The second analysis utilized six regressions that estimated the average difference in total government payments in 2017 for Black farms compared to White farms. The regressions showed, on average, how much more or less money Black farms received when some agricultural factors were held constant. Findings from the first analysis concluded that conditional on a particular farm size, the 2018 MFP payment eligibility was larger for Black farms rather than White farms. But, because black farms tend to be smaller on average, the average MFP payment among Black farms was smaller than for White farms. Black farms were eligible for a smaller 2018 MFP payment than White farms mainly due to their farm size compared to their yields and crops they grew. The second analysis found that Black farms received on average about $7,395 less in government payments in 2017 compared to White farms. About twenty percent of this gap can be explained by differences in farm size. Even after controlling for farm size, county, the farm’s location, gender of the farmer, and type of commodities produced, black farms still received on average $4,959 less government payments.
Keywords: Market Facilitation Program; Total Government Payments; United States Department of Agriculture; Black or African American producers; Minority producers